Preliminary Circuit Design for Robotics Environment Mapping Utilizing Ambient Light, Reflected Light and Stationary Infrared Radiation - Adrian, Leslie (Electrical, Control and Communication Engineering, 2011)
The paper deals with robotics mobility and a proposed topology for the acquisition of the necessary data to enable accurate mapping of a given environment, be that for basic maneuverability, (obstacle avoidance) or for higher level applications such as fire detection or item location. The topology is composed of a four layered system of analogue components which lends itself not only to excellent linearity but allows the system to control peripheral devices directly through any logic configuration, or to provide data needed for microcontrollers and their user defined algorithms. The various layers have been analyzed through simulation and to date confirmed though physical observation of the working model. The conclusions about the prospective solution are made.